Kirigami Cross-Shaped 3D Buckling Active Sensor for Detecting Stretching and Bending - Miao, L; J Wan; H. Guo; Wang, H; Y. Song; X. Chen; H. Zhang (2019 20th International Conference on Solid-State Sensors, Actuators and Microsystems Eurosensors XXXIII (TRANSDUCERS EUROSENSORS XXXIII), 2019)
Stretchable and movable 3D structure is a great choice for sensing stretching and bending. This paper reports a novel cross-shaped 3D buckling strain sensor based on polydimethylsiloxane (PDMS) substrate for detecting stretching and bending. Using pre-stretched PDMS, cross-shaped Polyimide (PI) film with conductive silver paint on its top surface as a 2D precursor can pop up as a dynamic 3D structure and possesses capacitive effect and triboelectric effect under different stretching and bending, which can detect stretching directions, strain value, bending axis direction and radius of curvature simultaneously, showing great potential in human and robot applications.